Strategic Leadership and Organizational Learning - Vera, Dusya; Crossan, Mary (Academy of Management Review, 2004)
Adopting the strategic leadership perspective, we develop a theoretical model of the impact of CEO and top manager leadership styles and practices on organizational learning. We take a fine-grained look at the processes and levels of organizational learning to describe how strategic leaders influence each element of the learning system. Researchers have implicitly assumed transformational leadership approaches to organizational learning. We challenge this conventional wisdom by highlighting the value of transactional leadership as well.